Awareness and understanding of girl child domestic helpers' employers on the issue of child labor - Gasataya, Jorelyne L.
The study sought to determine the awareness and understanding of employers of young domestic workers on the issue of child labor in the domestic service. Specifically, it sought to determine : (1) the factors influencing young girls to enter domestic service ; (2) the employers' criteria for employment or hiring of domestic helpers, (3) the employers' understanding of child labor; (4) employers' awareness on the issues of child labor; (5) the sources of information on the factors influencing their awareness; and (6) the implications of this awareness in the treatment of girl child domestic helpers.